2015
DOI: 10.1097/jto.0000000000000675
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Mutation Impact on Definitive Concurrent Chemoradiation Therapy for Inoperable Stage III Adenocarcinoma

Abstract: Concurrent CRT resulted in shorter progression-free survival in EGFR-mutant stage III adenocarcinoma patients than in wild-type patients, mainly because of distant metastasis relapse, regardless of better local control. Because of these distinct biological features, a different strategy, including EGFR-tyrosine kinase inhibitors for EGFR-mutant locally advanced adenocarcinoma patients receiving definitive CRT may be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 24 publications
6
83
0
Order By: Relevance
“…A total of seven retrospective studies were identified [ 22 28 ]. RT was used as the only preoperative therapy in one study, which was thus excluded from further analysis [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of seven retrospective studies were identified [ 22 28 ]. RT was used as the only preoperative therapy in one study, which was thus excluded from further analysis [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Ochiai et al 26 found no differences in the objective response rate (odds ratio 1.46, 95% CI 0.79-2.70) or the disease recurrence rate (odds ratio 1.37, 95% CI 0.68-2.75) after CRT between the EGFRm+ and EGFR wild-type groups. On the other hand, Tanaka et al 27 reported that PFS was significantly shorter in the EGFRm+ group and that the ratio of distant metastasis in patients with disease recurrence was relatively higher in this group than the EGFR wild-type group. We also observed a higher ratio of distant metastasis in the EGFRm+ group than the EGFRm−/unknown group.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study PFS was shorter and recurrence rate was higher in the EGFR mutant group, which was inconsistent with data from previous studies. Only one study, Tanaka et al (18), demonstrated that the PFS was shorter and 2-year recurrence-free survival rate was poorer in the EGFR mutant group. Notably, the recurrence patterns in these studies subsequent to cCRT in LA-NSCLC setting were similar to those of the present study, which demonstrated that the EGFR mutant groups exhibited lower loco-regional recurrence rate (15,16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study, Tanaka et al (18), demonstrated that the PFS was shorter and 2-year recurrence-free survival rate was poorer in the EGFR mutant group. Notably, the recurrence patterns in these studies subsequent to cCRT in LA-NSCLC setting were similar to those of the present study, which demonstrated that the EGFR mutant groups exhibited lower loco-regional recurrence rate (15,16,18). Preclinical studies have demonstrated that NSCLC cell lines with EGFR mutations exhibit greater radiosensitivity compared with those without EGFR mutation.…”
Section: Discussionmentioning
confidence: 99%